Teknologi Pendidikan: Efektivitas Penggunaan Media Pembelajaran Berbasis Teknologi Di Era Digitalisasi - Belva Saskia Permana; Lutvia Ainun Hazizah; Yusuf Tri Herlambang (Pusat Riset dan Inovasi Nasional, 2024)
Education in the era of digitalization has undergone significant changes with the use of technology-based learning media. This study aims to evaluate the effectiveness of using technology-based learning media in the context of education in the digital era. The results of the analysis show that the use of technology-based learning media can increase student engagement, understanding of concepts, and learning motivation. In addition, this approach allows easier access to a wide range of learning resources and allows for more adaptive learning according to individual needs. However, the results also reveal several challenges, including the need for proper training for teachers and students, as well as the need to mitigate security and privacy-related risks in the use of technology. The study concludes that, while recognizing the positive potential of technology-based learning media, it is important to design and implement effective strategies to ensure that technology is used optimally in educational contexts.